Calcium signaling regulates apoptosis-induced proliferation in Drosophila - Suthar, Komal Panchal; Hounsell, Caitlin; Fan, Yun; Bergmann, Andreas (PLOS Biology, 2026)
The initiator caspase Dronc can trigger apoptosis-induced proliferation (AiP), a specific form of compensatory proliferation. This study shows that Dronc-dependent Ca2+ influx into the cytosol is an important contributor of AiP and activation of the NADPH oxidase DUOX in Drosophila, and that this process may be conserved in vertebrates.